Immigration, Female Labour Supply and Local Cultural Norms - Jonas Jessen; Sophia Schmitz; Felix Weinhardt (Institute of Labor Economics (IZA), 2023)
We study the local evolution of female labour supply and cultural norms in West Germany in reaction to the sudden presence of East Germans who migrated to the West after reunication. These migrants grew up with high rates of maternal employment, whereas West German families mostly followed the traditional breadwinner-housewife model. We find that West German women increase their labour supply and that this holds within households. We provide additional evidence on stated gender norms, West-East friendships, intermarriage, and child care infrastructure. The dynamic evolution of the effects on labour supply is best explained by local cultural learning.
Keywords: J16; J21; D1; 330; gender; local learning; cultural norms; immigration